If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7x+4(x-7)=-37
We move all terms to the left:
-7x+4(x-7)-(-37)=0
We add all the numbers together, and all the variables
-7x+4(x-7)+37=0
We multiply parentheses
-7x+4x-28+37=0
We add all the numbers together, and all the variables
-3x+9=0
We move all terms containing x to the left, all other terms to the right
-3x=-9
x=-9/-3
x=+3
| 14+6n=3n-1 | | X-12=x/3 | | -4n=-84 | | 210-y=46 | | 177=9-x | | 74-2x=84-3x | | x-1=-7+x-x | | 3(x-1)+2x=11-1 | | 56=-8(u+1) | | -5(x–10)=-35 | | 202=64-u | | 18v-9v=81 | | -9(y-2)=2y-15 | | X=49/x | | 34-2x=45-7x | | 20,000x+0.08=50,000x+0.05 | | 4w+5=-3 | | 4k-1=-7+2k | | –9(x–4)=81 | | 248=148-x | | -9(x=4)=81 | | 6-18x=-36-4x | | 7n=-60-3n | | -3x+5=-6 | | 270=2x+4/3x | | –9(x–4)=81 | | X+9=-7x-15 | | 76-v=193 | | 157=-v+286 | | 2a^2-3a-27=0 | | 5–2c=1 | | 3(x-4)-(5-2x)=5(2x-1)-27 |